Does Teacher Collaboration Improve Student Achievement? Analysis of the German PISA 2012 Sample - Mora-Ruano, Julio Gregorio; Heine, Jörg-Henrik; Gebhardt, Markus (Frontiers in Education, 2019)
During the past decades, teacher collaboration has received increasing attention from both the research and the practice fields. However, little has been said about its relationship with student achievement. In the present study, using data from the representative PISA 2012 German sample, we investigate the effects that the three forms of teacher collaboration proposed by PISA namely instruction- project- and organisation related have on student achievement. We conducted exploratory and confirmatory factor analysis to test the factorial validity of the instrument. After some re-specifications to the questionnaire, the results from a full structural equation model suggest that a small positive effect can be seen, only when teachers specifically discuss student achievement. Implications for research and praxis are also presented and discussed.